Impact of lobular carcinoma in situ on local recurrence in breast cancer treated with breast conservation therapy: a systematic review and meta‐analysis. Issue 9 (26th February 2021) - Harris, Christopher G.; Eslick, Guy D.
Abstract: Background: Lobular carcinoma in situ (LCIS) is a known risk factor for breast cancer of unclear significance when detected in association with invasive carcinoma. This meta‐analysis aims to determine the impact of LCIS on local recurrence risk for individuals with breast cancer treated with breast conservation therapy to help guide appropriate management strategies. Methods: We identified relevant studies from five electronic databases. Studies were deemed suitable for inclusion where they compared patients with invasive breast cancer and concurrent LCIS to those with breast cancer alone, all patients underwent breast conservation therapy (lumpectomy with adjuvant radiation therapy) and local recurrence was evaluated. Recurrence data were pooled by use of a random‐effects model. Results: From 1488 citations screened by our search, nine studies were deemed suitable for inclusion. These studies comprised 990 cases and 12 870 controls. Median follow‐up time was 104 months. There was a significantly increased risk of overall local recurrence of breast cancer for individuals with LCIS in association with breast cancer following breast conservation therapy (pooled odds ratio (pOR) 1.73; 95% confidence interval (CI) 1.10–2.71; P = 0.018). The risk of local recurrence was not significantly increased at 5 years (pOR 1.00; 95% CI 0.49–2.04; P = 0.995) and 10 years (pOR 1.52; 95% CI 0.72–3.23; P = 0.275). Conclusion: Individuals with LCIS in association with invasive breast cancer have an increased risk of local recurrence following breast conservation therapy. This supports consideration of increased medical surveillance and exploration of further risk reduction strategies for such patients. Abstract : This meta‐analysis aimed to determine the impact of lobular carcinoma in situ (LCIS) on local recurrence risk for individuals with breast cancer treated with breast conservation therapy. Using a random‐effects model, it was shown that individuals with LCIS in association with invasive breast cancer have an increased risk of local recurrence following breast conservation therapy.